Perbedaan Hasil Belajar Siswa pada Penerapan Model Problem Based Learning dan Inquiry Learning serta Discovery Learning - Qurrotul A’yuni; Sugeng Pradikto (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
In this study, the goal is to compare the academic results of economics students from Pasuruan Public Secondary School 3 classes, which use the PBL learning model, inquiry-based learning and discovery-based learning. Consistent with the description of unequal groups, this study used an experimental methodology that included three types of trials, each using a unique teaching model. An analysis of the pretest and posttest results was carried out to identify possible differences in the academic performance of the students. Although several teaching models were implemented, The findings showed that there was no significant difference in academic performance across the three groups. The Kruskal-Wallis test produces an Asymp value. signature. of 0.274, which means there is no significant difference between learning models. Therefore, the application of the PBL, inquiry and discovery learning model can be said to have no significant effect on student academic achievement.